Pendugaan Evapotranspirasi Padi Sawah Dengan Metode Nisbah Bowen - Roberto I. C. O. Taolin; Impron Impron; Rini Hidayati; Bregas Budianto (Savana Cendana, 2017)
The objectives of this experiment were to test the accuracy of the Bowen ratio method of predicting actual evapotranspiration value of paddy rice. The case study in Indramayu regency, held from June to September 2012. The weather components measured by the Bowen Nisbah system are net radiation, wet ball and dry ball temperature, wet ball gradient and the dry ball at altitudes between 140 cm and 160 cm and at altitudes between 160 cm and 180 cm and soil heat flux. Measurements every 30 minutes from 6.00 AM to 6.00 PM. The components measured by AWS are radiation, temperature, humidity, air pressure, rainfall, wind direction, and speed. The daily evapotranspiration value estimated with Bowen ratio was compared to the correspondent value obtained from FAO Penman-Monteith method using a paired t-test. Results shown the rice field daily evapotranspiration in Indramayu measured at a dry period during the second growing season estimated with Bowen ratio method was 3.3 mm, ranging from 2.4 to 4.3 mm. The corresponding values estimated with the FAO Penman-Monteith was 3.5 mm, ranged from 2.4 to 4.6 mm. The daily evapotranspiration values estimated with two approaches were comparable.